Mechanical Scarification Influence on Gleditsia assamica Bor Water Uptake and Germination - Farid Kuswantoro; Arrohmatus Syafaqoh Li’aini (Biosaintifika: Journal of Biology & Biology Education, 2022)
Physical dormancy is a typical kind of dormancy in Fabaceae species, including Gleditsia assamica. Physical dormancy is caused by the impermeability of the seed coat and can be alleviated, among others, by mechanical scarification. Previous studies on mechanical scarification effect on G. assamica seed focus only on its germination parameter without regard to its effect on seed water upatke. As germination is initiated with water uptake, current study aims to understand the treatment effect on both of seed water uptake and germination parameters. Tetrazolium dyeing and seed weight measurement trials were conducted to study the seed water uptake. Meanwhile, a germination test is conducted to investigate the treatment's influence on the seed germination parameters. This study shows that mechanical scarification can enhance G. assamica seed water uptake. The treatment was also significantly improve final germination percentage and germination speed index. This study result gives us a clearer understanding of the effect of mechanical scarification to alleviate G. assamica dormancy and germination, which will be advantageous to the species conservation and domestication efforts.